Mutation Screening of the GLE1 Gene in a Large Chinese Cohort of Amyotrophic Lateral Sclerosis Patients - Li, Yanran; Sun, Bo; Wang, Zhanjun; He, Zhengqing; Yang, Fei; Wang, Hongfen; Cui, Fang; Chen, Zhaohui; Ling, Li; Wang, Chaodong; Huang, Xusheng (Frontiers in Neuroscience, 2021)
Amyotrophic lateral sclerosis (ALS) is a fatal progressive neurodegenerative disease involving the upper and lower motor neurons of the spinal cord, brainstem, and cerebral cortex. At least 30 genes have been implicated in familial ALS (fALS) and sporadic ALS (sALS). Kaneb et al. (2015) first carried out a large-scale sequencing study in ALS patients and identified two loss-of-function (LOF) variants in the GLE1 gene. The LOF mutation-induced disruption of RNA metabolism through the haploinsufficiency mechanism is implicated in ALS pathogenesis. A total of 628 ALS patients and 522 individuals without neurodegenerative disorders were enrolled in this study to explore the GLE1 gene contribution to ALS in the Chinese population. All 16 exons and the flanking intron of GLE1 were screened by Sanger sequencing. In total, we identified seven rare GLE1 coding variants, including one novel nonsense mutation and six rare missense mutations in 628 ALS patients. The frequency of GLE1 LOF mutations was 0.16% (1/628) among Chinese sALS patients, implying that it is an uncommon genetic determinant of ALS in Chinese patients. Additionally, the rare missense variants in the hCG1-binding domain of GLE1 impairing the distribution of the hGle1B isoform at the nuclear pore complex (NPC) region may be involved in the pathogenesis of ALS.